2018
DOI: 10.1111/eip.12743
|View full text |Cite
|
Sign up to set email alerts
|

Does rTMS reduce depressive symptoms in young people who have not responded to antidepressants?

Abstract: Aim Depression is common in young people, and there is a need for safe, effective treatments. This study examined the efficacy of repetitive transcranial magnetic stimulation in a sample of young people aged 17 to 25 years. Methods This retrospective study included 15 people aged 17 to 25 years referred by their private psychiatrists affiliated with Ramsay Health Care, South Australia Mental Health Services. All patients met Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition criteria for tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 37 publications
2
19
0
Order By: Relevance
“…There were no differences found in recovery rates between males and females, or age. While there has been previous research that showed younger patients responded better to rTMS (Pallanti et al, 2012), a number of studies have been unable to show any difference in rtMS response between both age and gender (Conca et al, 2000;Ciobanu et al, 2013;Rosenich et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…There were no differences found in recovery rates between males and females, or age. While there has been previous research that showed younger patients responded better to rTMS (Pallanti et al, 2012), a number of studies have been unable to show any difference in rtMS response between both age and gender (Conca et al, 2000;Ciobanu et al, 2013;Rosenich et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 outlines the study characteristics of the 14 studies included in the review, 8 of these studies were open-label trial studies, totalling N = 142 adolescent participants with depression receiving rTMS treatment (Bloch et al, 2008;Croarkin et al, 2016;Dhami et al, 2019;MacMaster et al, 2019;Rosenich et al, 2019;Wall et al, 2011;Yang et al, 2014;Zhang et al, 2019). The remaining 6 studies were either post-hoc analyses studies (using these existing open-trial datasets) (n = 5 studies) (Croarkin et al, 2018;Croarkin et al, 2012;Sonmez et al, 2019;Wall et al, 2016) and one study (Mayer, Aviram, Walter, Levkovitz, & Bloch, 2012) was a three-year follow-up of one of the open-trial studies (see Table 1 for specific details of datasets used in these studies).…”
Section: Summary Of Included Studiesmentioning
confidence: 99%
“…Thirteen studies included adolescents with a diagnosis of treatment-resistant depression (TRD) (Bloch et al, 2008;Croarkin et al, 2018;Croarkin et al, 2016;Croarkin et al, 2012;Dhami et al, 2019;MacMaster et al, 2019;Mayer et al, 2012;Rosenich et al, 2019;Sonmez et al, 2019;Wall et al, 2016;Wall et al, 2013;Wall et al, 2011;Yang et al, 2014) and only one study included adolescents diagnosed with either a mood or anxiety disorder (i.e., not TRD) (Zhang et al, 2019). At baseline, all these clinical diagnoses were verified in line with the Diagnostic and Statistical Manual for Mental Disorders (DSM-IV) criteria (APA, 2000) using either the Mini-international Neuropsychiatric Interview (Sheehan et al, 1998) or the Kiddie Schedule for Affective Disorders and Schizophrenia Present and Lifetime version (K-SAD-PL) (Kaufman et al, 1997).…”
Section: Samplesmentioning
confidence: 99%
See 2 more Smart Citations